POLA PENATAAN RUANG DALAM USAHA-USAHA KONSERVASI PADA WILAYAH HUTAN MANGROVE DI DAERAH TELUK PRIGI KABUPATEN TRENGGALEK - -, Maroeto; Suhardjono, Hadi (MAPETA, 2002)
Mangrove was a special type of forest ecosistym; it was influence by many factors especially human factor . People around mangrove forest have positive and negative interaction will cause mangrove crush. The aim of this study was manage and conserve the mangrove forest to sustain the mangrove forest at Prigi area and maintain the function of forest ecosystem as nursery ground for fish and another species of water animal. The method of this study was survei method to classivied , analize and grouping the homogenaus area. This study conducted at Prigi area ( + 15.444 ha ) at 8 11 - 8 23 Is and 111 41 – 111 44 BT , for 5 months (Pebruary 1999 - Juny 1999 ) . Physical and chemical analysis was done at soli science laboratory Agriculture Faculty UPN “Veteran” Jatim and Brawijaya Univ. Brawijaya Univ Malang. The conclusion was (a) Mangrove forest was for ENlay from housing (b) It has wide estuarine for beach ecosystem (c) Sedimentation was low. It was showed that there is no erosion at dowload of stream. (d) Mangrove eapacity to catch the silt was diminish. As the result, sea water was dirty and cause sedimentation . Finally, sea habitat was change and diminishing the amount of fish at Prigi area